Interpolating South Asian spaces and transnational habitation in Tanuja Desai Hidier’s born confused - Manohari Rasagam,; Shanthini Pillai, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2015)
While there in an exhaustive list of literature produced by diasporic South Asian writers that voices a multitude of concerns for both men and women of this descent, the voice that speaks to the South Asian young adult needs to be highlighted and explored in detail. This is especially crucial as the majority of metropolitan young adult texts are largely Eurocentric in nature. Novels with themes that appeal to a young reader with subject matter consistent with the age, experiences and challenges of the young adult and with a young non-white protagonist are rare. This paper introduces a South Asian Diasporic Metropolitan Young Adult text to investigate how it can interpolate into the consciousness of the Metropolitan diasporic South Asian young reader as well as into the western narrative space. This is done by focusing on the ways in which South Asian elements of place, history, and allegory interpolate into the narrative space of Tanuja Desai Hidier’s young adult novel, Born Confused (2002). The ultimate aim of this paper is to show that South Asian Diasporic Metropolitan Young Adult Literature can play a role in interpolating transnational heritage by creating an awareness of cultural heritage on familiar young adult grounds and decenter Eurocentric narrative discourses.